Manajemen Konflik Sekolah Regrouping Di SD Negeri Pucangsawit Surakarta - Suwarto Suwarto (Faculty of Teacher Training and Education, Universitas Muhammadiyah Surakarta, 2016)
The objectives of the research are to describe: 1) the sources and types of conflict; 2) the conflicts’ management; and 3) the supporting and inhibiting factors in conflict management of regrouped school at State Elementary School Pucangsawit Surakarta. The type of the research is qualitative with naturalistic design. The research was undertaken atState Elementary School Pucangsawit Surakarta. The results are 1) the conflict sources at State Elementary School Pucangsawit Surakarta can be classified into two types of sources, namely the teachers and parents. The conflict types emerged at the form of inter-individual conflict among teachers from the regrouped schools, the conflict in school naming, conflict related to professional tasks and teachers’ administration, and conflict related to students’ administration; 2) the conflict management at State Elementary School Pucangsawit Surakarta were done through planning, organizing, actuating, and controlling. The conflict resolution referring to schools’ rivalry is done by applying fair and positive competition; and 3) the supporting factors in conflict management are the government support and schools’ stakeholder’s awareness. The inhibiting factors cover the self ego that remains existed in some teachers and parents from both of the schools regrouped.